Using societal conditional regard to cope with drug use in the ultraorthodox community and the unintended consequences - Itzhaki-Braun, Yael; Gavriel-Fried, Belle (Frontiers in Psychology, 2024)
Introduction A developing theoretical framework for the investigation of tight cultures’ reaction toward members who violate communal norms is societal conditional regard (SCR). Methods Using a qualitative interpretive approach, in the current study we investigated the way the Ultraorthodox Jewish community uses SCR to cope with substance use disorders (SUDs), which considered to be a norms violation in closed religious communities. We did so by drawing on in-depth interviews with 14 young men from the Ultraorthodox community in Israel who were diagnosed as having an SUD and were in recovery. Results (a) The community’s socialization process, educating its members to lead a life that is the only right one; (b) The community’s use of God as the one whose love and regard are conditional; (c) The SCR emotional and behavioral practices used by the community toward individuals who violate norms, and (d) How, paradoxically, the use of SCR may eventuate in the initiation of drug use, and within the community itself. Discussion Findings are discussed in the context of self-determination theory and SCR, and shed light on how tight cultures cope with the threat of deviation of communal norms. Implications for intervention and policy are outlined.